The Treatment of Haitian Bahamians in Bahamian Society - Joseph, Fiona (International Journal of Bahamian Studies, 2014)
Originally presented as an informal paper at a discussion panel on Statelessness, this paper outlines some of the policies that hinder Haitian Bahamians from participating in mainstream society, the stigma that is attached to such policies and the unethical standpoint that justifies them. It briefly touches on migration and focuses on the issues of nationality and citizenship.